PHYSIOTHERAPY INTERVENTIONS ON DEFORMITIES CAUSED BY LEPROSY (Fiep Bulletin - online, 2013)
Introduction: Leprosy, formerly known as Hansen's disease or disease, is a chronic infectious disease caused by Mycobacterium leprae, and manifests itself through skin lesions presenting with decreased or absent sensation. In addition to skin manifestations, leprosy has important repercussions on peripheral nerves. Clinically, neuritis can be silent and no signs or symptoms, or may be evident, sharp, accompanied by severe pain, hypersensitivity, swelling, and loss of sensitivity paralysis of muscles. Objective: Aim of physiotherapy intervention in neurites and disabilities generated by Hanseniase. Methodology:: bibliographic study through search sites Bireme scientific, and Pubmed Scielo with descriptors leprosy disease process and public health. Selected articles that focused on the disease process and the social determinants of patologia. Results: Being the leading cause of leprosy permanent physical disability among infectious diseases due to neuritis, early treatment is the only way to prevent neuropathy. Monitoring the sensitivity and muscle strength is needed to prevent from prophylactic or reparative process, disabilities. The activities of prevention and treatment of physical disabilities should integrate the treatment of leprosy. All health professionals should be alert to diagnose and promptly treat any evidence of neural injury in order to prevent disabilities futuras. Conclusion: There is no case report in the literature regarding the specific physical therapy for leprosy, so the therapist must make a protocol treatment to improve the problems of the sequelae caused by the disease, if they already exist, or even prioritize the prevention of the sequelae deformities and most prevalent disease.
Keywords: Physiotherapy; Hansen Disease; Physical Incapacity